Critical Pedagogy and Identifying Muslim Identity in a Digital Age. - Hussien, Suhailah (2019)
The paper aims to explore how the practice of critical pedagogy in an Undergraduate class helped my students to identify their Muslim identity amidst challenges living in the 21st century of a globalised world. The phenomenological study examines the engagement of 12 Muslim students in a practice based class through discourse analysis. Using the movie, ‘Searching..’ I employed critical pedagogy to question, analyse and challenge our practices (my students and mine) of social networking. The study found that the engagement in critical pedagogy has helped them to be critical of their perceptions and practices of social networking. The study also found that students identified a sense of belonging and an ‘in group sameness’ in terms of their responses to popular culture and interactions in social media. The Muslim students’ responses and interactions were varied but tend to converge into a salient pattern, i.e. bordered within their’ conscience and critical consciousness as Muslims, identifying Islam as the tie that binds them in their personal identification and collective association. The study too discovered that engaging in critical pedagogy did not only result in raising my students’ criticality, but it also challenged and changed my views, knowledge and practices of social networking in a more positive way.